Salvage Therapy With Selpercatinib for RET-Rearranged NSCLC With Pralsetinib-Related Pneumonitis and Leptomeningeal Disease: A Case Report - Paolo D. d'Arienzo, MD, MRCP; Niamh Cunningham, MBBS, BSc, MRCP; Hazel O’Sullivan, MBBchBAO, MRCPI; Charlotte Grieco, MBBS, MRCP; Virjen Patel, MbChB, BSc, FRCR; Sanjay Popat, PhD, FRCP (JTO Clinical and Research Reports, 2023)
Selpercatinib and pralsetinib are RET inhibitors with substantial activity in advanced RET-rearranged NSCLC. We present a case of pralsetinib-related pneumonitis and leptomeningeal and brain metastases progression during treatment suspension for pneumonitis. During recovery, selpercatinib administration led to rapid neurologic response and complete intracranial response and allowed pneumonitis resolution. This case supports the safety of selpercatinib in patients with pneumonitis on pralsetinib and highlights its marked efficacy in leptomeningeal disease.